2004
DOI: 10.1016/j.jvolgeores.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Fluid circulation and structural discontinuities inside Misti volcano (Peru) inferred from self-potential measurements

Abstract: One of the seven potentially active andesite stratovolcanoes in southern Peru, Misti (5822 m), located I 7 km northeast and 3.5 km above Arequipa, represents a major threat to the population (-900,000 inhabitants). Our recent geophysical and geochemical research comprises an extensive self-potential (SP) data set, an audio-magnetotelluric (AM1) profile across the volcano and CO 2 concentrations in the soil along a radial profile. The SP survey is the first of its kind in providing a complete mapping of a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 29 publications
5
85
2
1
Order By: Relevance
“…The high oxidation state preserved by the gases further indicates limited interaction with low temperature rock (Giggenbach, 1987). The absence of contamination of the dome gas composition by hydrothermal fluids is consistent with the idea of Finizola et al, (2004) who suggested that the hydrothermal system at El Misti is sealed by hydrothermal alteration. The clear magmatic signature and high equilibrium temperature of the emitted gases, together with their high exit temperature (270-310°C), suggest a relatively shallow magmatic source (see model from Stevenson, 1993).…”
Section: Discussionsupporting
confidence: 80%
“…The high oxidation state preserved by the gases further indicates limited interaction with low temperature rock (Giggenbach, 1987). The absence of contamination of the dome gas composition by hydrothermal fluids is consistent with the idea of Finizola et al, (2004) who suggested that the hydrothermal system at El Misti is sealed by hydrothermal alteration. The clear magmatic signature and high equilibrium temperature of the emitted gases, together with their high exit temperature (270-310°C), suggest a relatively shallow magmatic source (see model from Stevenson, 1993).…”
Section: Discussionsupporting
confidence: 80%
“…The first magmatic gas to exsolve from the magma, CO 2 , rises preferentially through magma and country rock along the main structural faults (e.g., Finizola et al, 2004;Chiodini et al, 2005;Bruno et al, 2007). While atmospheric CO 2 concentrations range from~350 to 500 ppm, magmatic gas can generate CO 2 concentrations from b1% to >95% within the soil pore spaces (e.g., Williams-Jones et al, 2000;Federico et al, 2010).…”
Section: Soil Co 2 Concentrationmentioning
confidence: 99%
“…SP anomalies have been observed on active volcanoes with an amplitude ranging from a few hundreds millivolts up to several volts (Michel and Zlotnicki, 1998;Finizola et al, 2004;Aizawa, 2008;Barde-Cabusson et al, 2012;Brothelande et al, 2014). Saturated ground water flow is usually considered as the main process (so-called electrokinetic phenomenon) inducing the SP signal (Malengreau et al, 1994;Michel, 1998;Aubert et al, 2000;Finizola et al, 2004;Ishido, 2004;Bedrosian et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Saturated ground water flow is usually considered as the main process (so-called electrokinetic phenomenon) inducing the SP signal (Malengreau et al, 1994;Michel, 1998;Aubert et al, 2000;Finizola et al, 2004;Ishido, 2004;Bedrosian et al, 2007). Electrical lows located at the periphery of the volcano are interpreted to be related to saturated meteoric water downflow.…”
Section: Introductionmentioning
confidence: 99%